Design of photonic microcavities in hexagonal boron nitride - Kim, Sejeong; Toth, Milos; Aharonovich, Igor (Beilstein Journal of Nanotechnology, 2018)
We propose and design photonic crystal cavities (PCCs) in hexagonal boron nitride (hBN) for diverse photonic and quantum applications. Two dimensional (2D) hBN flakes contain quantum emitters which are ultra-bright and photostable at room temperature. To achieve optimal coupling of these emitters to optical resonators, fabrication of cavities from hBN is therefore required to maximize the overlap between cavity optical modes and the emitters. Here, we design 2D and 1D PCCs using anisotropic indices of hBN. The influence of underlying substrates and material absorption are investigated, and spontaneous emission rate enhancements are calculated. Our results are promising for future quantum photonic experiments with hBN.
Keywords: anisotropic optical materials; boron nitride; photonic crystals